2010
DOI: 10.1111/j.1365-2648.2010.05511.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication between children and health professionals in a child hospital setting: a Child Transitional Communication Model

Abstract: Children prefer to oscillate between a passive bystander and active participant position within the communication process, depending on their needs at any given point in time. This challenges the insistence for stronger child participation in all matters that affect them, in isolation of debates surrounding children's need for support/protection and any potential negative consequences of children's active participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 51 publications
4
43
1
1
Order By: Relevance
“…In the contemporary study, children appreciated handing over responsibility to their parents at times and sharing decision-making with them. This finding is in accordance with previous studies by Lambert et al [24,25], who found that children want to waver between being a “passive bystander” and an “active participant” in the communication process, depending on the situation. Children often want to be involved and to participate in and to contribute to shared decision-making.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the contemporary study, children appreciated handing over responsibility to their parents at times and sharing decision-making with them. This finding is in accordance with previous studies by Lambert et al [24,25], who found that children want to waver between being a “passive bystander” and an “active participant” in the communication process, depending on the situation. Children often want to be involved and to participate in and to contribute to shared decision-making.…”
Section: Discussionsupporting
confidence: 93%
“…During the last few decades, studies have been performed with instead of on children. These studies have provided new and important knowledge about, for instance, children’s experiences with regard to the hospital environment [21-23], communication [24,25], consultation [26], short-term illnesses [27,28], chronic illnesses in general [29], and diabetes [30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be a relevant tailored intervention to help improve communication during medical visits, according to specific demands of parents and children, which is in agreement with literature (Aburn & Gott, 2011;Coyne & Gallagher, 2011;Coyne & Harder, 2011;Howells & Lopez, 2008;Lambert et al, 2011;Ringnér et al, 2010;Zwaanswijk et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
“…Another relevant aspect highlighted by the literature are the individual preferences for the kind and amount of information, which is related to the adaptation to treatment and satisfaction with health services, endorsing the need for tailored interventions that may contribute to the development of better interactions between pediatricians, caregivers, and children (Aburn & Gott, 2011;Coyne & Gallagher, 2011;Coyne & Harder, 2011;Howells & Lopez, 2008;Lambert, Glacken, & McCarron, 2011;Ringnér, Jansson, & Graneheim, 2010;Zwaanswijk et al, 2011). Therefore, psychosocial interventions are important in order to understand the triadic interaction and provide better communication in pediatric settings.…”
mentioning
confidence: 99%
“…Os estudos apresentam a focalização de demandas individuais como elemento que facilita adaptação ao tratamento e satisfação dos usuários (Coyne & Gallagher, 2011;Lambert, Glacken, & McCarron, 2011;Nestel, Taylor, & Spender, 2004;Ranzani, 2009;Ringnér et al, 2010;Zwaanswijk et al, 2011). Especifi camente no caso de doenças crônicas pediá-tricas, momentos distintos do tratamento podem requerer informações específi cas, corroborando a relevância da comunicação sob medida (Kästel et al, 2011).…”
Section: Inclusão De Temas Psicossociais Na Interação E Preferências unclassified